Functional significance of axonal Kv7 channels in hippocampal pyramidal neurons - Mala M. Shah; Michele Migliore; Ignacio Leyva-Valencia; Edward C. Cooper; David A. Brown (2008)
Members of the Kv7 family (Kv7.2–Kv7.5) generate a subthreshold K + current, the M− current. This regulates the excitability of many peripheral and central neurons. Recent evidence shows that Kv7.2 and Kv7.3 subunits are targeted to the axon initial segment of hippocampal neurons by association with ankyrin G. Further, spontaneous mutations in these subunits that impair axonal targeting cause human neonatal epilepsy. However, the precise functional significance of their axonal location is unknown. Using electrophysiological techniques together with a peptide that selectively disrupts axonal Kv7 targeting (ankyrin G-binding peptide, or ABP) and other pharmacological tools, we show that axonal Kv7 channels are critically and uniquely required for determining the inherent spontaneous firing of hippocampal CA1 pyramids, independently of alterations in synaptic activity. This action was primarily because of modulation of action potential threshold and resting membrane potential (RMP), amplified by control of intrinsic axosomatic membrane properties. Computer simulations verified these data when the axonal Kv7 density was three to five times that at the soma. The increased firing caused by axosomatic Kv7 channel block backpropagated into distal dendrites affecting their activity, despite these structures having fewer functional Kv7 channels. These results indicate that axonal Kv7 channels, by controlling axonal RMP and action potential threshold, are fundamental for regulating the inherent firing properties of CA1 hippocampal neurons.